Postoperative complications of vaginal operations. - Coz Carranza, Javier (2015)
Between July 10, 1973 to September 30, 1974, inclusive, 183 vaginal operative procedures were performed pelvic dystopia in the Gynecology Department of the Central Hospital No. 2 among them being the front and back colporrhaphy the most commonly used. Bladder drainage system used was the retention Foley catheter type, administering antibiotics prophylactically. They were seen as more important immediate post operative complications urinary tract infection (38.2%) and reimplantation catheter (29.5%). The methods proposed in the prevention of these complications are reviewed.